A modular cloud-based ontology framework for context-aware EHR services. (22nd July 2019) - AlSobeh, Anas M.R.; Hammad, Rafat; Al-Tamimi, Abdel-Karim
Healthcare providers in a heterogeneous distributed environment depend on many non-functional requirements or cross-cutting concerns that could affect the entire Healthcare Information System (HIS). The implementation of crosscutting concerns could potentially lead to a significant impact on the integrity of Electronic Health Records (EHRs), as well as code quality. Aspect-Oriented Programming (AOP) encapsulates the crosscutting concerns to improve the overall quality of software development by reducing the required code to implement collection modules. In this paper, we propose an AOP-based novel approach to improve the elasticity of cloud-based EHR services. We propose an abstract framework for cloud-based HIS, which provides EHR interoperability through incorporating crosscutting concerns. The proposed framework eliminates the need to change the core code by adding high-level abstractions to complex cloud applications. We implement a prototype of the proposed framework to validate its ability in both separation of concerns and the ability to reuse EHR services.